Multiple deformation mechanisms induced by pre-twinning in CoCrFeNi high entropy alloy. (15th January 2022) - Zhang, Zhen; Jiang, Zhihao; Xie, Yuehuang; Chan, Sammy Lap Ip; Liang, Jiamiao; Wang, Jun
Abstract: Multiple deformation mechanisms in high entropy alloy have been a notable method to overcome strength-ductility trade-off dilemma, but they usually occur in some severe conditions such as cryogenic temperature. Here, we triggered the multiple deformation mechanisms in room temperature tensile test by introducing "pre-twins" in CoCrFeNi high entropy alloy via cryogenic deformation and annealing. The deformation microstructures at strains of 1%, 5% and 15% were investigated by electron back scattering diffraction and transmission electron microscopy. The results demonstrated that at the strain of 5% or more, besides dislocation slip, microbanding and deformation twinning also occured due to the high flow stress facilitated by the pre-twins, which increased the working hardening ability, leading to a simultaneous increase of strength and ductility. The deformation process and the underlying mechanisms of the microbanding and twinning have been discussed in comparison with the CoCrFeNi high entropy alloy sample without twins. Graphical abstract: Image, graphical abstract